2009
DOI: 10.1016/j.worlddev.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

David Versus Goliath: The Impact of Chinese Competition on Developing Countries

Abstract: una copia impresa con un costo de $500 si es dentro de Chile y US$12 si es para fuera de Chile. Las solicitudes se

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 30 publications
7
56
2
Order By: Relevance
“…There is no evidence of a positive effect on productivity from many robust estimates even our sample included only survival firms. 10 Our finding is consistent with Federico (2014), who find no positive effect of import penetration from low-wage countries on firm employment, the wage bill and outputs in Italy's manufacturing firms those with low tech advancement, and Alvarez and Claro (2008) who find no positive effect of rising import penetration on firm productivity in Chilean manufacturing firms. Unlike most research on Downloaded by [FU Berlin] at 06:31 02 July 2015 developed countries, in Vietnam as well as in Chile capital and skilled labours are scarce, which impedes or makes it costly for product upgrading.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…There is no evidence of a positive effect on productivity from many robust estimates even our sample included only survival firms. 10 Our finding is consistent with Federico (2014), who find no positive effect of import penetration from low-wage countries on firm employment, the wage bill and outputs in Italy's manufacturing firms those with low tech advancement, and Alvarez and Claro (2008) who find no positive effect of rising import penetration on firm productivity in Chilean manufacturing firms. Unlike most research on Downloaded by [FU Berlin] at 06:31 02 July 2015 developed countries, in Vietnam as well as in Chile capital and skilled labours are scarce, which impedes or makes it costly for product upgrading.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…The rising imports from China lead to higher unemployment, increasing retirement and unemployment benefits, and also trigger declines in wages, employment and household earnings. Alvarez and Claro (2008) provide probably some of the first evidence from a developing country, namely Chile. Like Vietnam, Chilean manufacturing firms face more intense competition from China as they produce similar products and are presumably low-productivity and low-skilled labour intensive plants.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…caused many of these small workshops to close down because they could not compete with these imports; their members, therefore, had to disperse and individually look for other sources of income 5 . This is supported by empirical evidence: in their analysis of the impact of increased Chinese imports on the Chilean manufacturing sector, Álvarez and Claro (2009) found that the former negatively affect employment growth as well as the chances of survival of manufacturing plants while firms have limited ability to escape these imports. In another article, Álvarez and Opazo (2011) highlight a significant decrease www.iap-socent.be in relative wages in sectors-and especially small firms-exposed to higher Chinese-import penetration.…”
Section: (B) the Rise And Fall Of Popular Economy In Chilementioning
confidence: 87%
“…The rapid ascent of China in the last decade as the global manufacturing nation ‘giant’ intensified this situation even further. An increase in Chinese exports is a worldwide phenomenon that generates important questions regarding its impact on the rest of the world, especially in labour‐intensive industries where China is believed to concentrate its comparative advantage (Álvarez and Claro, ). The integration of low‐wage countries into the world trading system has been among the most important economic developments of recent decades (Federico, ).…”
Section: Introductionmentioning
confidence: 99%